Nonfluoroscopic catheter ablation in patients with atrial fibrillation - O. V. Sapelnikov; D. F. Ardus; V. S. Kostin; T. M. Uskach; D. I. Cherkashin; I. R. Grishin; K. B. Bogatyreva; A. V. Emelyanov; A. A. Kulikov; O. A. Nikolaeva; R. S. Akchurin (Российский кардиологический журнал)
The article demonstrates available literature data on the nonfluoroscopic catheter ablation of atrial fibrillation (AF). The main disadvantages of standard fluoroscopic catheter ablation are shown. The research results on the use of intracardiac echocardiography are presented. The first experience of using the fluoroscopy-free procedure in Russia as a pilot study is also presented. During the period from December 2017 to December 2019, 28 radiofrequency ablations and 40 pulmonary vein cryoballoon ablations were performed without fluoroscopy using threedimensional imaging and intracardiac echocardiography. Despite the small number of large studies in this area, clinical cases described in the literature, as well as their own results, demonstrate the safety of using three-dimensional imaging in combination with intracardiac echocardiography as an alternative to fluoroscopy. Application of the approach is of undoubted practical interest and requires further study in large studies.